KECEMASAN MAHASISWA PERAWAT SEBELUM MENGIKUTI UJIAN KETRAMPILAN DI LABORATORIUM - Suyanto Suyanto; Retno Isrovianingrum (Jurnal Ilmiah Kesehatan, 2018)
Introduction: Implementation of skills evaluation in the laboratory is necessary to see how far the ability has been achieved. Objective structured clinical examination (OSCE) becomes one of the evaluation techniques used. the purpose of this study is to know prevalence of the anxiety and the factors that cause anxiety before following the OSCE in first-degree nursing students. Methodology: This research is a descriptive research, as many as 89 respondents selected by using simple random sampling. The questionnaire used was Nursing Skills Anxiety Scale Test (NSTAS). Results: 65 respondents (73%) experienced anxiety with most of the sexes were women (89,9%), and 56 respondents (62.9%) were 18 years old. Factor’s related to anxiety included environment (50,5%), exam it self (44,9%) and observer (44,9%). Discussion: there is a need for further research on the impact of anxiety before taking the OSCE examination with graduation rates on each skill performed